Development and evaluation of winter barley varieties for group resistance to smut diseases - I. B. Legkun (Вавиловский журнал генетики и селекции, 2015)
The problem of the immunity of winter barley varieties to smut diseases is still urgent in the agricultural practice. The first varieties bred by PBGI – NCSCI (Ukraine) that possessed complex disease resistance to smut diseases were Zimovyi (2005), Dostoinyi, Trudivnyk, Selena Star, and Aborihen (2006). They were followed by Akademichnyi, Aivenho (2012), Burevii (2013), Snigova koroleva (2014), and Deviatyi val (2015). They were all developed with the participation of donors s.i. 13664 and Dzhau Kabutak; however, the nature of the group resistance remained insuffi- ciently studied. The objectives of this work were the study of the topical problem of smut diseases in winter barley in Southern Ukraine, elucidation of the nature of group resistance to false loose smut and covered smut species in the donors s.і. 13664 and Dzhau Kabutak, and development of new highly productive breeding material resistant to smut diseases. According to the results of this study it was found that the yield loss caused by the direct and hidden losses depending on the level of susceptibility- resistance of the variety could be as large as 44,1 %. The study revealed a monogenic dominant control of the resistance to false loose smut and covered smut species. The proportion of recombinants in the F2 generation of a double analyzing cross varied from 5,1 to 9,5 %. Our opinion is that there was an incomplete linkage of the inheritance of resistance genes. When developing resistant breeding material we tested an integrated approach combining several principles. In doing this, we tried the following method: natural infection with local populations of false loose smut (Ustilago nigra) and covered smut (Ustilago hordei) against artificial background (in the field) followed by the test (invasive) assessment of the variety samples at the stage of competitive variety trial.